Resilience evaluation of the environmental control and life support system of a spacecraft for deep space travel - Matelli, José Alexandre [UNESP]; Goebel, Kai (Elsevier, 2018)
In deep space manned travels, the crew life will be totally dependent on the environment control and life support system of the spacecraft. A life-support system for manned missions is a set of technologies to regenerate the basic life-support elements, such as oxygen and water, which makes resilience a paramount feature of this system. The resilience of a complex engineered system is the ability of the system to withstand failures, continue operating and recover from those failures with minimum disruption. Resilient design is a new design framework on which the main goal is to quantify system resilience upfront in order to guide the design team during the conceptual design stage. In this article, we present a tool that combines a rule-based approach with a Monte Carlo-based approach to evaluate the resilience of a proposed environment control and life support system designed for deep space travel. Based on the results found, we explore a few design alternatives in order to increase system resilience.
Keywords: Conceptual design; Deep space; Life support; Resilience; Resilient design